Scenario 3: hydrogen apogee - narrative and strategic recommendations - Costa, Francisco De Sousa Lima Frias (2022)
In the subsequent Work Project, a scenario was built based on a deductive evaluation of a potential supply strategy for green hydrogen. The framework for Dortmund Energy and Water Supply GmbH's (DEW21) future strategic alternatives was established by researching the external environment and conducting interviews with three essential experts. The reader is introduced into a possible future for the hydrogen sector, as well as the threats and opportunities that may emerge within the specified time frame. Finally, comprehensive strategy advice is provided to the company.